STUDENTS’ PERCEPTIONS OF USING INSTAGRAM REELS AS MOBILE-ASSISTED LANGUAGE LEARNING TO IMPROVE SPEAKING SKILLS - Hikmah, Nur; Hidayati, Hidayati; Irwandi, Irwandi; Ilham, Ilham; Rahmaniah, Rima; Whitworth, Nicole (University of Kuningan, 2024)
Instagram is one of the mobile apps to assist language learning. The most widely used social networking platform globally right now is Instagram. This study aimed to investigate the perspective of university students on using Instagram reels as mobile-assisted language learning to improve speaking skills whether they had a negative or positive perception of it. This study utilized a descriptive qualitative approach and the research instrument used a closed and open-ended questionnaire with 66 respondents from the first until the seventh semester. This study found that the majority of students have a positive perception of using Instagram reels in speaking skills. Students believe that this tool is comfortable and fun to develop a new atmosphere in learning to speak, it also increases their motivation because Instagram reels provide interesting content for improving their speaking skills, they can find many Instagram accounts that post more about English lessons with short duration even though students sometimes get a distract cause of random video but they already know their own goals to practice consistently every day and everywhere. Through this tool, students gain a lot of vocabulary from the video, quotes, caption, or comment section that is very helpful for them to improve their speaking performance especially when they are engaged in communication with other people both inside or outside classroom practice.